Kerangka Kerja Indikator Pengukuran Tingkat Kematangan Transformasi Digital Perguruan Tinggi - Yanuar Firdaus Arie Wibowo; Dawam Dwi Jatmiko Suwawi; Widia Febriyani (STMIK Budi Darma, 2022)
Strategic planning is an essential part of the college life cycle; a critical aspect of planning is the digital transformation of universities. Digital transformation supports university business processes and is a riving engine for universities to adapt to changes to provide added value for the best services for all stakeholders. To achieve this, universities need an overview of the maturity level of digital transformation that has been achieved today. This research produces a new methodology for assessment in a holistic framework as an indicator of measuring the maturity level of digital transformation.This measuring tool must be easy to use by universities when they will take measurements for all academics and easily understood by all respondents who are determined to provide an accurate picture of the maturity level of digital transformation. The final result is presented in the form of a framework that contains a standard value index of maturity level, and recommendations for digital transformation as a form of self-evaluation for higher education strategic planning